1983
DOI: 10.1104/pp.71.4.828
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Fern Rhizoid Elongation by Metal Ions and the Function of the Spore Coat as an Ion Reservoir

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Ca is taken up over this time, however, since the gametophytes are assimilating carbon and the Ca content is expressed relative to the dry weight. Ca is needed later for rhizoid growth (18) and protonema development (4). The R-stimulated increase in total intracellular Ca can be reversed by a subsequent irradiation with FR indicating that the increase in intracellular Ca is mediated through phytochrome (Table III).…”
Section: Wayne and Heplermentioning
confidence: 99%
“…Ca is taken up over this time, however, since the gametophytes are assimilating carbon and the Ca content is expressed relative to the dry weight. Ca is needed later for rhizoid growth (18) and protonema development (4). The R-stimulated increase in total intracellular Ca can be reversed by a subsequent irradiation with FR indicating that the increase in intracellular Ca is mediated through phytochrome (Table III).…”
Section: Wayne and Heplermentioning
confidence: 99%
“…The germination can take place in spores hydrated in just water (15), but it has been indicated that ions, particularly Ca2", present in the spore coat play essential roles for germination (16,17,24,25). In fact, spores become strictly dependent on the supply of external Ca2+ when treated with the Ca2+ chelator, EGTA (17,24 2 Abbreviations: R, red light; FR, far-red light; GO, G1, and S, the phases of the cell cycle.…”
mentioning
confidence: 99%
“…Figure 7 also shows the effect ofpCa on primary rhizoid elongation. Ca ++ is also required for spore germination in Onoclea sensibilis (Miller and Wagner, 1987) and Adiantum capillusveneris (lino, Endo, and Wada, 1989). Ca ++-uptake via ion channels is required for cytokinin-induced bud formation in the moss, Funaria hygrometrica (Conrad and Hepler, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The standard medium used for the culture of gemmaẽ as Knop's medium (Miller and Greany, 1974), pH adjusted to 5.3-5.4, and prepared with twice-distilled water and reagent grade salts. EGTA was from Sigma Chemical Co, St. Louis, Missouri.…”
Section: Methodsmentioning
confidence: 99%